2012
DOI: 10.1021/jm300452p
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Selective LRRK2 Inhibitors Guided by Computational Analysis and Molecular Modeling

Abstract: Mutations in the genetic sequence of leucine-rich repeat kinase 2 (LRRK2) have been linked to increased LRRK2 activity and risk for the development of Parkinson's disease (PD). Potent and selective small molecules capable of inhibiting the kinase activity of LRRK2 will be important tools for establishing a link between the kinase activity of LRRK2 and PD. In the absence of LRRK2 kinase domain crystal structures, a LRRK2 homology model was developed that provided robust guidance in the hit-to-lead optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 62 publications
4
87
1
Order By: Relevance
“…The inhibitors were also assayed for inhibition of Janus kinase 2 (JAK2), as previous efforts had confirmed that JAK2/LRRK2 biochemical selectivity correlated with biochemical selectivity against the broader kinome. 22,23 The 3-and 5-amino-linked pyrazoles (2 and 3) demonstrated good JAK2/LRRK2 selectivity but appeared to have inferior potency for LRRK2 in our biochemical screen and cell-based LRRK2 autophosphorlyation assay when compared to the 4-linked aminopyrazoles (5−7). The poor JAK2 selectivity of compound 4 (2.7×) confirmed that a nitrogen lone pair (e.g., compound 2) or 3-/5-substituent was required to achieve good selectivity.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 93%
See 1 more Smart Citation
“…The inhibitors were also assayed for inhibition of Janus kinase 2 (JAK2), as previous efforts had confirmed that JAK2/LRRK2 biochemical selectivity correlated with biochemical selectivity against the broader kinome. 22,23 The 3-and 5-amino-linked pyrazoles (2 and 3) demonstrated good JAK2/LRRK2 selectivity but appeared to have inferior potency for LRRK2 in our biochemical screen and cell-based LRRK2 autophosphorlyation assay when compared to the 4-linked aminopyrazoles (5−7). The poor JAK2 selectivity of compound 4 (2.7×) confirmed that a nitrogen lone pair (e.g., compound 2) or 3-/5-substituent was required to achieve good selectivity.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 93%
“…Additionally, our lead optimization efforts toward 1 established the importance of occupying the vector adjacent to the hingebinding anilino N-H motif (methoxy group in 1) for overall kinase selectivity. 22,23 The incorporation of this "selectivity handle" was one of the major considerations in the design of possible aniline replacements. Lastly, the morpholine carboxamide moiety occupies a solvent-exposed region of the active site.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on a "best" template to build LRRK2 kinase domain homology models due to the fact that the kinases for which X-ray crystal structures have been published have at most 30% sequence identity to LRRK2. The most common templates have been from B-Raf [94,101,[129][130][131], JAK-2 [132][133][134][135][136][137][138], MLK1 [132,[136][137][138][139], ROCO4 [131,140], and TAK1 [132,141,142] kinases, chosen based on overall kinase sequence identity, ATP-binding site identity, and/or crossover of inhibitor activity. Consensus from these alignments is that G2019 is the Gly in the conserved DFG motif (DYG in LRRK2) and I2020 is the subsequent residue in the activation loop (Fig.…”
Section: Kinase Domain Pathogenic Mutationsmentioning
confidence: 99%
“…Mutation of A2016 to Thr abolishes activity in some inhibitors [35,140,143], but not others [145][146][147], which is indicative of the inhibitor binding modes. The non-conserved residues L1949, S1954, R1957, and F1883 were identified as potential selectivity handles in the LRRK2 kinase domain, due to their proximity to the ATP-binding pocket for a series of diaminopyrimidine compounds [132][133][134][135]. L1949 near the hinge region was targeted for selectivity since it is a smaller residue than Phe or Tyr, which is found in this position in approximately 60% of the kinome.…”
Section: Using Lrrk2 Structure To Guide Kinase Inhibitor Designmentioning
confidence: 99%
“…16 This residue is a Tyr or Phe in the JAK family ( Figure S3). By directing a methyl (35) or ethyl (36) substituent in this direction, TMLR potency and wtEGFR selectivity were comparable to 13, but markedly increased selectivity against JAK1 was realized, with a modest improvement in JAK2 selectivity for compound 36 (Table 3).…”
mentioning
confidence: 99%